Enhancing empathy among medical students via reflective writing (Canadian Medical Education Journal, 2024)
Implication StatementReflection is a skill which has the potential to enhance higher order thinking such as empathy and compassion. We aimed to study reflective writing as a means to nurture empathy among medical students. An interventional study was conducted among 73 final-year medical students using the Toronto Empathy Questionnaire. The questionnaire was administered anonymously before and after a clinical clerkship. Reflective writing generated strong emotional responses but did not improve Empathy Questionnaire scores. Reflective writing about patient care experiences may be useful in clinical clerkships to develop certain constructs of empathy such as perspective taking and compassion among medical students, but it may not raise empathy scores in the short term.